"I feel like just a normal person now": An exploration of the perceptions of people with intellectual disabilities about what is important in the provision of positive behavioural support. (2nd July 2018) - McKenzie, Karen; Whelan, Kathryn J.; Mayer, Claire; McNall, Anne; Noone, Steve; Chaplin, Jill
Accessible Summary: People with a learning disability do not always get good support We wanted to know what they thought about positive behavioural support They told us many important things about good and bad support Good support included being treated as a human being, having a good and full life and being helped with behaviour and skills. Abstract: Background: There is a growing evidence base about the effectiveness of positive behavioural support (PBS) in relation to behaviours that challenge (CB). There is, however, limited research from the perspective of individuals receiving this support. The objective of this qualitative study was to obtain the views of participants with an intellectual disability about what was important to them in relation to receiving PBS. Materials and methods: Seven participants with an intellectual disability, recruited via support organisations in the North East of England, gave their views about their support through interviews ( n  =   3) and a focus group ( n  =   4). Data were collected between April and June 2016 and were analysed using thematic analysis. Results: Four themes were identified: the importance of being treated as a human being; the wider impact of PBS; the contrast of PBS with previous experiences of support; and the beneficial impact of positive support. PBS was valued for its wide impact on quality of life, with a reduction in CB being just one of many important aspects. Conclusion: This study highlights the importance of including service user perspectives and quality‐of‐life indicators in research which evaluates service provision and support.